Participation and/or/ against tacit knowledge: ILAUD, 1976–1981 - Lonergan, Hamish (Interstices: Journal of Architecture and Related Arts, 2023)
For several productive years from 1976 to 1981, the International Laboratory of Architecture and Urban Design (ILAUD) engaged with the issue of participation in architecture and planning in the city of Urbino. Each year, these summer workshops—founded by Giancarlo De Carlo in 1976—brought together students, educators, and prominent practitioners from across the fields of architecture, urban planning, architectural history, and art to discuss and experiment on the issue of how designers should engage with users of the built environment. In this sense, the workshop’s participants were explicitly united against what De Carlo derided as formalism, and later as eclecticism and postmodernism. At the same time, despite this broad consensus, ILAUD’s public outputs—the student work and lecture transcripts collated in the annual reports—seem to betray a set of disagreements between participants from various European and North American schools and between planners and architects. On one side, were a group of schools who argued that participation involved an analysis of the built fabric and cultural heritage of a city and its architecture; on the other, those who believed that participation required the direct involvement of future users. Yet, rather than accepting these as fundamental differences in attitude, this paper uses such apparent contradictions to argue that these various approaches were united in articulating a new, broader, and more equitable relationship between users, clients, and designers, on the cusp of postmodernity.